PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HP VIVO YANG DIMEDIASI OLEH CITRA MEREK - Zulfiqar Nugraha; Netti Nurlenawati; Dexi Triadinda (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
The cellphone industry in Indonesia is experiencing very tight competition dynamics, marked by the emergence of the Transsion group which has begun to shift the market share of established brands such as Vivo. Despite having a spec advantage, Vivo faces significant market pressure. This study aims to evaluate the contribution of product quality to the purchase decision of HP Vivo by placing brand image as a mediating variable. Through a quantitative approach, this study involved 120 workers at PT Bridgestone Tire Indonesia as respondents. The number of respondents was determined by hair theory through the purposive sampling method. The sample criteria are workers who have bought Vivo brand cellphones. Data analysis techniques with R-square, F-square, path coefficients and hypothesis testers on direct and indirect influences through SmartPLS 3 software. The findings of the study revealed that there is a significant correlation between product quality and brand image, as well as the real contribution of brand image to purchasing decisions. Furthermore, product quality has been proven to have a significant impact on purchase decisions, both directly and through the mediation of brand image. This indicates that even though quality is able to stimulate transactions independently, the influence will be much more optimal if it is supported by a positive brand image.